Checks and Balances, Private Information, and the Credibility of Monetary Commitments - Keefer, Philip (World Bank, Washington, DC, 2013)
The authors develop and test several new hypotheses about the anti-inflationary effect of central bank independence and exchange rate pegs in the context of different institutions and different degrees of citizen information about government policies. Theory provides strong reason to believe that while central bank independence will prove more effective as a commitment mechanism in countries where multiple players in government have veto power (checks and balances), the number of veto players will have no effect on the credibility of exchange rate pegs. Conversely, the authors argue that central bank independence does not solve the problems of commitment that arise when citizens are imperfectly informed about the contribution of government policy to inflation. Exchange rate pegs, however, mitigate these problems. The authors present extensive evidence from cross-country tests using newly developed data that provide strong support for their propositions.